2016
DOI: 10.1080/13102818.2015.1133254
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of polysaccharide and triterpenoid production ofGanoderma lucidumthrough mutagenesis of protoplasts

Abstract: Ganoderma lucidum is a traditional medicinal macrofungus in China, which has two kinds of key bioactive compounds -polysaccharides and triterpenoids. To improve the polysaccharide and triterpenoid production from G. lucidum, the preparation and regeneration conditions of protoplasts were optimized. This was done by systematic trials with various parameters, and protoplast mutation was subsequently performed. A mycelium that was cultivated for seven days and treated with 0.33 mL of 1% snailase and 0.66 mL of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…and Benjaminiella poitrasii, in which higher protoplast integrity was achieved using 0.6 M KCl as an osmoprotector (Coelho et al 2010 ; Cheng and Bélanger 2000 ; Chitnis and Deshpande 2002 ). The properties and composition of cell walls differ in different fungal species and may vary depending on environmental conditions, which, in turn, necessitates experimental selection of the osmotic stabilizers used and their concentrations, as well as lytic agents and lysis conditions for protoplast generation (Patil and Jadhav 2015 ; Gow et al 2017 ; Li et al 2017 ; Peng et al 2016 ). Previously when protoplast obtaining from G. zeae 5373 and ATCC 20,273 strains, the most effective combinations of lytic enzymes were chitinase plus β-glucuronidase yielding up to 1 × 10 5 /mL protoplasts (Adams et al 1987 ; Adams and Hart 1989 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Benjaminiella poitrasii, in which higher protoplast integrity was achieved using 0.6 M KCl as an osmoprotector (Coelho et al 2010 ; Cheng and Bélanger 2000 ; Chitnis and Deshpande 2002 ). The properties and composition of cell walls differ in different fungal species and may vary depending on environmental conditions, which, in turn, necessitates experimental selection of the osmotic stabilizers used and their concentrations, as well as lytic agents and lysis conditions for protoplast generation (Patil and Jadhav 2015 ; Gow et al 2017 ; Li et al 2017 ; Peng et al 2016 ). Previously when protoplast obtaining from G. zeae 5373 and ATCC 20,273 strains, the most effective combinations of lytic enzymes were chitinase plus β-glucuronidase yielding up to 1 × 10 5 /mL protoplasts (Adams et al 1987 ; Adams and Hart 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal protoplast mutation is known to be a fast and convenient method providing high sensitivity to stimulation, high mutation rate, and simplicity of the screening procedure (Peng et al 2016 ). The use of N -methyl- N' -nitro- N -nitrosoguanidine (NTG) or UV light irradiation are the most common methods of fungal protoplast mutagenesis (Wilmańska et al 1992 ; Shafique et al 2009 ; Besoain et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Liu et al, 2011 ). Chemical mutagens lithium chloride or the combination of lithium chloride with Triton X-100 have treated the protoplasts of the G. lucidum for enhancement the production of polysaccharides and triterpenoid ( Peng et al, 2016 ). For the multiple genes induced by the chemical mutagens and also dangerous for users who usually exposed to high (methylnitronitrosoguanidine and ethyl methanesulfonate) or very high toxicity (sodium azide and ethidium bromide).…”
Section: Breeding Techniquesmentioning
confidence: 99%
“…For example, Peng et al reported that the use of lithium chloride (a chemical mutagen) to treat Ganoderma lucidum protoplasts led to the highest yields of intracellular polysaccharides and triterpenoids, which were 37.50 and 40.81 mg/g, respectively. These were 568.45% and 373.43% higher than those of the original strain, respectively [ 32 ]. For the physical mutagens, a conventional way is to utilize ionizing radiation or heavy-particle-beams.…”
Section: Introductionmentioning
confidence: 99%